P-moment stability of power system under small Gauss type random excitation. (December 2015) - Lu, Zhanhui; Zhao, Weixiang; Xie, Di; Li, Gengyin
Highlights: The p -moment ( p ≥ 2) stability theorem for a kind of stochastic system is proved. Our theorem is a generalization of the previous conclusion for mean square stability. The stability of an OMIB system under random excitation is analyzed by our theorem. The significance of higher-order moment is related to skewness and kurtosis. Abstract: The stability of power systems in the uncertain environment has been increasingly concerned. The main discussion in this paper is the p -moment stability of power system under small Gauss type random excitation. By Lyapunov method, Ito isometry formula, matrix theory and so on, the p -moment stability theorem of stochastic models is proved when p is greater than or equal to 2. The previous conclusions of mean square stability are particular cases of our p -moment stability theorem. Taking a one machine and infinite bus system as a simulation example, using Euler–Maruyama numerical method, the angle curves under random excitation were simulated. The p -moment stability of the power system under Gauss type of random small excitation are verified and illustrated by simulation samples.